IMPROVING HEALTH INFORMATION OF PREGNANT MOTHERS WITH THE ISLAMIC FAMILY APPROACH THROUGH THE RECOGNITION OF ANEMIA SIGNS - Dewi Andariya Ningsih; Siti Romlah; Susiana; Umi Nur Kholifah; Tiara Indriani; Silaturrohmih; Siti Hilmi Musyarrofah; Siti Nurhidayati (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
The most direct cause of maternal death is bleeding. Bleeding is divided into two categories, namely antepartum bleeding (vaginal bleeding at 28 weeks of gestation or more) and postpartum hemorrhage (bleeding that occurs within the first 24 hours after delivery). Bleeding occurs due to lack of supervision and examination during pregnancy, including prevention of anemia. Mothers who suffer from anemia in pregnancy will be very susceptible to infection and bleeding, even if the bleeding is only a little. Experience has shown that maternal death due to bleeding is more common in women who suffer from anemia. Anemia often occurs due to iron deficiency because pregnant women have a twofold increase in iron requirements due to an increase in blood volume without expansion of plasma volume, to meet the needs of the mother (prevent blood loss during childbirth) and fetal growth. Anemia is a condition where the hemoglobin level (>11(gr/L)2), hematocrit (>0.33gr/L), and red blood cell count are below normal values. Anemia in pregnancy is the biggest public health problem that occurs worldwide, especially in developing countries, in low socio-economic groups, and has a very large influence on the quality of human resources. Anemia in pregnancy is called